Systematic Review of Institutional Belonging and Motivation as Predictors of Long-Term Student Success - Lydia Githinji,; Daphine Nyangoma, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This systematic review explores the roles of institutional belonging and motivation as predictors of long-term student success. As higher education institutions seek to enhance student outcomes, understanding the factors that contribute to persistence, academic achievement, and post-graduation success is critical. Institutional belonging refers to the extent to which students feel connected to their academic and social environments, while motivation is typically categorized as intrinsic or extrinsic, driving engagement and goal-setting behaviors. Both factors have been shown to influence students' academic performance, retention rates, and overall well-being, but their combined effects on long-term success remain underexplored. This review synthesizes findings from a range of studies, focusing on the impact of belonging and motivation on academic persistence, career readiness, and professional development. Key studies were selected based on specific criteria, including peer-reviewed articles that explore longitudinal outcomes, motivation, and belonging in student populations. The review highlights that a strong sense of belonging contributes to improved academic engagement, lower dropout rates, and enhanced mental health, while intrinsic motivation fosters persistence and academic excellence. Furthermore, this review identifies the synergistic effects of these factors, showing how a sense of belonging can strengthen intrinsic motivation, creating a positive feedback loop that further enhances long-term success. The review concludes with recommendations for educators and institutional leaders to prioritize strategies that nurture both belonging and motivation, such as peer mentoring, inclusive teaching practices, and personalized student support. Future research is needed to explore these relationships across diverse populations and educational settings to refine interventions and maximize student success outcomes.
Keywords: Systematic review; Institutional; Motivation; Predictors; Long-term; Student success